Comparing the dominant and continuous theoretical frameworks of spatial microgenesis - Aber, Jeremy W. (Kansas State University, 2012)
The theoretical framework of spatial microgenesis as presented by Siegel and White (1975), and updated by Montello (1998) posits that through exposure, humans will create spatial knowledge of places in their minds. This process is thought to be an ongoing one, and will eventually lead to a metrically-scaled ‘map-like’ image in the mind. In Siegel and White’s dominant framework, knowledge of space progresses through the stages of landmark and route, and ends with survey knowledge, whereas in Montello’s continuous framework, metrically-scaled survey knowledge is present from the first exposure. Beyond that primary difference between the two theoretical frameworks, the continuous framework also provides for greater nuance in how the process may occur for different individuals. There is little research directly addressing the differences between the two frameworks, and this dissertation adds support for the continuous framework by testing three of its five tenets. Utilizing a virtual environment as a laboratory, participants were exposed to a novel environment and asked to complete spatial tasks based on knowledge of the layout of said environment. Over the course of three sessions, measures of spatial knowledge were recorded using distance, direction, and sketch map tasks. The results support the first tenet of the continuous framework: metrically-scaled survey-type knowledge was found in all participants beginning with the first session. The concepts of landmark, route, and survey knowledge are still valuable though, as the results clearly showed that they help to describe the way that individuals conceptualize mental representations of space. These conceptualizations may potentially be valuable as a component of a larger spatial ontology for the American public school system. Regarding tenet two, some improvement in error rates was observed over time, but not at a statistically significant rate for all tasks, suggesting that other factors such as the study length and motivating factors may have played a role in performance. Tenet four was also supported, with significant variation in performance between participants with similar levels of exposure to the environment. Overall, this dissertation finds that the continuous framework is largely correct in its descriptions of the process of spatial microgenesis, albeit with some elements that are not fully supported by the data collected. Despite not being a good model of the process, the dominant framework remains valuable for describing how people conceptualize their spatial knowledge of environments.
Keywords: Spatial microgenesis; Spatial cognition; Behavioral geography; Geography; Geographic education; Geography (0366)